Continuous-infusion vancomycin therapy for preterm neonates with suspected or documented Gram-positive infections: a new dosage schedule. Issue 6 (1st May 2008) - Plan, O; Cambonie, G; Barbotte, E; Meyer, P; Devine, C; Milesi, C; Pidoux, O; Badr, M; Picaud, J C
Abstract : Background: Intermittent infusion of vancomycin is widely used to treat late-onset sepsis in neonates. On the other hand, the continuous infusion of vancomycin could improve bactericidal efficacy since its action is time dependent. Objective: To evaluate a simplified dosage schedule for continuous-infusion vancomycin therapy. Methods: Prospective study in premature neonates (<34 weeks) with suspected coagulase-negative staphylococci (CoNS) sepsis. Before antibiotics at time zero (T0), serum creatinine was measured and blood cultures were collected. Vancomycin dosage began with 25 mg/kg/day or 15 mg/kg/day (period 1) and 30 mg/kg/day or 20 mg/kg/day (period 2) depending on whether serum creatinine was below or above 90 μmol/l. Two days after beginning treatment (first timepoint: T1), serum vancomycin was measured and second blood cultures were collected. Results: Between June 2002 and December 2005, 145 neonates were evaluated. At birth, the median (interquartile range) body weight was 920 (500–1160) g and gestational age was 28 (26–29) weeks. At T1, serum vancomycin was within the required range in 74.5% of neonates (108/145). Serum vancomycin levels were higher in period 2 than in period 1 (20 mg/l vs 13 mg/l, p<0.05). At T0, 55% (80/145) of blood cultures were positive for CoNS, but 71% (57/80) were negative at T1. Four days after beginning treatment, 92% of subjects had recovered without removing the central venous catheter. Conclusion: Using this simplified dosage schedule, bactericidal efficacy was maintained and most subjects had serum vancomycin concentrations within the therapeutic range.